(untitled) (Revista Científica Integrada, 2024)
Objective: to relate healthy eating to the prevention of anxiety and depression in adults. Methods: Palavras-chave: Transtorno afetivo bipolar. COVID-19. Saúde mental. Fenomenologia. Psicopatologia. systematic review conducted using the keywords “mental disorders”, “depression”, “anxiety”, “mental health”, “Diet, food and nutrition”, “Feeding behavior” and “Prevention”. All searches in electronic databases were carried out on April 22, 2023, and articles published in the last five years were selected, following the PRISMA protocol. Of the 140 articles searched, a selection was made that culminated in a sample of 20 articles, which met the inclusion criteria. Results: The study revealed that a healthy diet, especially the Mediterranean diet, is associated with a significant reduction in the risk of anxiety and depressive disorders in adults, highlighting the importance of the interaction between diet and intestinal microbiota for mental health. Conclusion: A healthier diet with a Mediterranean profile showed good evidence regarding the prevention of depressive disorders and reduction of anxiety but requires further studies regarding the diet profile and the association between depressive and anxiety disorders.